Risking sustainability: Political risk culture as inhibiting ecology-centered sustainability - Susan T. Jackson (Risks, 2021)
This exploratory study aims to understand why, and propose remedies for, the treatment of political risk and sustainability as siloed risk areas in risk analyses. I employ an interdisciplinary theoretical approach that focuses on the roles of values and worldviews, stages of sustainability and hybrid knowledge to understand this siloing. The large-N interpretive method used here combines content frequency counts with discourse analysis to examine over 400 corporate communication documents from 37 companies. The study also explores how, through corporate communication, companies that provide political risk analysis convey what is at risk and what counts as sustainability. I argue that the broad shared 'cultural' tones of what it means to be in the political risk field pose challenges for integrating political risk and sustainability. The study concludes with several recommendations on how to overcome the current barriers in order to integrate political risk and sustainability in risk analyses.
Keywords: 330; political risk; sustainability; epistemic culture; methodology